2002
DOI: 10.1080/10903120290938508
|View full text |Cite
|
Sign up to set email alerts
|

T Rauma H Elicopter E Mergency M Edical S Ervices T Ransport : A Nnotated R Eview of S Elected O Utcomes-Related L Iterature

Abstract: Based on its roots in military air evacuation, helicopter emergency medical services (HEMS) has always been emphasized as a tool for trauma transportation. Despite much discussion regarding resource allocation for HEMS, a literature search found little recent systematic review of pertinent studies. As HEMS utilization is subject to increased scrutiny in a health care dollar-conscious environment, it was felt that a compendium of available outcomes-related literature could assist those assessing utility of HEMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(14 citation statements)
references
References 1 publication
2
11
0
Order By: Relevance
“…Although the impact of HEMS and GEMS is still debated, our findings support the results of recent studies on HEMS with advanced statistics [1,2,7-10]. Actually, the ORs reported in those studies were very similar (Table 6).…”
Section: Discussionsupporting
confidence: 89%
“…Although the impact of HEMS and GEMS is still debated, our findings support the results of recent studies on HEMS with advanced statistics [1,2,7-10]. Actually, the ORs reported in those studies were very similar (Table 6).…”
Section: Discussionsupporting
confidence: 89%
“…Results have been variable, but most studies have shown outcome benefit. 1,3,4 One issue ubiquitous in the TRISS literature is the inability to randomize patients to air vs. ground transport with all the inherent weaknesses in observational, nonrandomized studies, which demonstrate elements of association and potentially unmeasured confounders. Without randomization, it becomes impossible to control for the multiple confounding variables that culminate in a patient's being selected for air vs. ground transport.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for the effectiveness of HEMS in both trauma and nontrauma settings has been the subject of much debate in the medical literature over the past two decades. [1][2][3][4] There has been increased scrutiny of air medical transport, which must justify itself in the light of growing safety and economic concerns. [5][6][7] While study methodologies evaluating HEMS in trauma have included observational studies, stratified analyses, and before-and-after studies, Trauma Injury Severity Score (TRISS)-based analyses have been the most commonly utilized study method.…”
Section: Introductionmentioning
confidence: 99%
“…In this setting, helicopter utilization and its effect on outcomes of TBI remain an issue of debate. 2–7 …”
mentioning
confidence: 99%